The institutional determinants of private equity involvement in business groups: The case of Africa - Bruce Hearn; Lars Oxelheim; Trond Randøy (Research Institute of Industrial Economics (IFN), 2015)
This study examines the governance attributes of post-IPO (initial public offering) retained ownership of private equity in business group constituent firms in contrast to their unaffiliated counterparts, in 202 newly listed firms in 22 emerging African economies. We adopt an actor centred institutional-theoretic perspective in rationalizing institutional voids and the advantages of maintained governance by both business angels (BA) and venture capital (VC) private equity. Our findings reveal private equity retain higher post-IPO ownership in business group constituents compared to unaffiliated firms and that this is inversely moderated in the context of improving institutional quality. Our result adds to the literature on multifocal corporate governance mechanisms.
Keywords: K00; G10; G30; G32; G34; G38; 330; Business Group; Business Angel; Venture Capital; Africa; IPO; Ownership Structure; Institutional Voids; Property Rights Protection